Measuring the effectiveness of individual therapy on the well‐being of children and young people who have experienced abusive relationships, particularly domestic violence: A case study. Issue 4 (2nd August 2018) - Perry, Sarah; Frampton, Ian
Abstract: Background: The evidence base regarding effective interventions for children and young people who experience abusive relationships, particularly domestic violence, is extremely limited. Aims: To evaluate the effectiveness of individual therapy for children and young people who have experienced abusive relationships; to address the challenges in carrying out such research. Methodology: A nonexperimental service evaluation repeated measures design with the administration of Routine Outcome Measures (ROMs) that assessed, skills, functioning and symptoms and experience of service. In total, 735 participants aged between 4 and 17 years were referred to the service. More than three quarters of those referred, attended at least three sessions and completed therapy. Results: The majority of those referred to the service presented with high needs. Mean scores on each of the ROMs improved and these changes were statistically significant. Based on clinical threshold scores, there was a deterioration for a small proportion of the sample (10% or less), improvements for between 28.5 and 49.4% and no change for the remainder. Statistical effect sizes, as measured by the ROMs, were generally in the medium range; satisfaction with the service was high. Implications: Gathering evidence to demonstrate the effectiveness, or not, of therapy is fraught with difficulties. In the research world, evaluation studies of "real world" interventions may be regarded as inferior to gold standard randomised controlled trials. However, such studies may be better at capturing everyday practice and what can be realistically achieved in terms of measuring effectiveness. There are important implications for commissioning and evaluating such interventions.